Cimetidine therapy does not prevent rebleeding from peptic ulceration. Issue 704 (June 1984) - Carr-Locke, D. L.; Taverner, D.; Wicks, A. C.
Abstract : One-hundred and five patients admitted to hospital with symptoms of acute upper gastrointestinal haemorrhage shown at endoscopy to be due to peptic ulceration were entered into a prospective double-blind controlled trial of cimetidine versus placebo therapy. The trial therapy was commenced within 12 hr of admission and continued for 7 days. Cimetidine therapy made no difference to the transfusion requirements, rebleeding rate or number of operations performed in patients with either gastric or duodenal ulcers, nor was it of benefit in patients aged over 65 years of age.